2013
DOI: 10.1007/s00268-013-2127-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Hepatocellular Carcinoma in Noncirrhotic Liver After Hepatectomy

Abstract: Recurrence is the most common cause of death after hepatectomy for HCC, and patients should undergo careful, long-term follow-up. Early detection and treatment of recurrence with curative intent should improve the prognosis of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
(50 reference statements)
1
20
1
Order By: Relevance
“…Consequently, in light of reduced number of serious complications, mean post‐operative hospital stay of almost 7 days was observed. These figures are lower than those reported by other series, with POM data from 36% to 55% and mortality from 3.7% to 6.5% …”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Consequently, in light of reduced number of serious complications, mean post‐operative hospital stay of almost 7 days was observed. These figures are lower than those reported by other series, with POM data from 36% to 55% and mortality from 3.7% to 6.5% …”
Section: Discussioncontrasting
confidence: 70%
“…These figures are lower than those reported by other series, with POM data from 36% to 55% and mortality from 3.7% to 6.5%. 12,[26][27][28][29][30][31] Post-operative hepatic insufficiency or post-resection liver failure may be due to scarce remnant liver tissue, prolonged ischaemia resulting from vascular control manoeuvres during surgery or a combination of both. Age (>65 years), complex surgeries, extension of the resection, duration of the Pringle manoeuvre and left hepatectomies 32,33 are all factors that have been associated with post-resection hepatic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that the long-term outcomes of HCC patients with cirrhosis are significantly worse than those without cirrhosis after LR [ 20 , 25 - 29 ]. The 5-year overall survival (OS) rate after LR for HCC in patients with advanced cirrhosis is less than 30%, whereas this rate is more than 50% in those without cirrhosis [ 20 , 30 , 31 ]. Taura and colleagues [ 20 ] compared the long-term outcomes of 127 HCC patients without cirrhosis with those of 129 patients with Child A cirrhosis and 37 with Child B cirrhosis according to the oncological Milan criteria.…”
Section: Reviewmentioning
confidence: 99%
“…Challenges in early HCC diagnosis mean that most cases are detected too late to be curable. Surgical resection remains the preferred treatment [3, 4], but postoperative recurrence is high [5]. Therefore, understanding how HCC recurs may allow the design of treatments or interventions to reduce it.…”
Section: Introductionmentioning
confidence: 99%